Microsporidia-induced stromal keratitis: a new cause of presumed immune stromal (interstitial) keratitis. Issue 5 (22nd December 2021) - Mohanty, Amrita; Behera, Himansu Sekhar; Barik, Manas Ranjan; Kaur, Amanjot; Sharma, Savitri; Das, Sujata; Fernandes, Merle; Panda, Sailendra; Sahu, Srikant K
Abstract : Background and objective: To describe the clinical features, diagnosis and management of immune stromal keratitis/interstitial keratitis (IK) associated with microsporidial epithelial keratitis. Methods: Between October 2020 and January 2021, medical records of IK patients microbiologically proven as microsporidia from samples collected from corneal epithelium on smear examination, and/ or molecular analysis were reviewed. Demography, clinical profile and treatment were analysed. Real-time PCR (RT-PCR) for adenovirus (ADV), Epstein-Barr virus (EBV), herpes simplex virus (HSV) and varicella-zoster virus (VZV) was done. Results: Twenty of 152 (13%) microbiologically proven cases of microsporidial keratitis were diagnosed as IK during the study period, the mean age and duration of symptoms were 35.7±11.4 years and 46.3±27.7 days, respectively. Half had predisposing risk factors, like trauma; and 30% had prior recurrences. One-fourth of patients were using antivirals on presentation. Characteristic presentations included disciform keratitis(n=12), incomplete/complete ring(n=5), and combination(n=3), along with variable subepithelial infiltrates (n=14). All cases had stromal oedema, with an intact epithelium and fine pigment dusting on endothelium. Corneal epithelial scrapings had scanty microsporidia spores in smears of 17/20 (85%), and pan-microsporidial DNA was identified in 14/20 (70%), with Vittaforma corneae by sequencing in 11/20 (55%). Other viruses detected were ADV (14, 70%), VZV (2, 10%), EBV (1, 5%) and HSV (1, 5%). Rapid resolution of inflammation and oedema within 2 weeks of starting steroids was seen in all cases. Conclusion: Microsporidia epithelial keratitis induced stromal inflammatory keratitis; is distinguished from microsporidial keratoconjunctivitis and stromal keratitis, by characteristic clinical features, and response to topical steroids.